THE USE OF SELF ASSESSMENT IN TEACHING WRITING PROCESS - Abdul Rohim (Universitas Muhammadiyah Tangerang, 2020)
The objective of this research is to give information and clear explanation about the use of self assessment in teaching writing process.. This research uses the descriptive qualitative research. The population of this research is all students of fifth semester for english study program in Muhammadiyah University of Tangerang.semester academic 2019/2020 consisting of four parallel classes namely class 5a1, 5a2, 5a3,and 4b1. Based on the research finding, it can be concluded that self assessment is effective in teaching writing self-assessment in writing learning (writing) aims to encourage students to reflect themselves on students' writing abilities. Self-assessment encourages students to think about the purpose of why students learn to write, and to know what and how they learn. And for the teacher should implement it in their class and it still needs further research in order to develop scientific references. Key words: Self Assessment, Writing